Etnomatematika dalam Proses Pembuatan Kertas Daluang di Kabupaten Indramayu - Taufan, Mochammad; Nurafifah, Luthfiyati; Gading, Gading (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research will explore the mathematical knowledge contained in the traditional elements of making Daluang paper in Indramayu Regency. This research was carried out at Rumah Daluang, the Indramayu Arts Council, and the Sawo Kecik Theater House as groups engaged in making Daluang paper in Indramayu. This research is qualitative research using an ethnographic approach. Data collection techniques used were interview, observation and documentation techniques. The validity of the data in this research will be tested through credibility, transferability, dependability and confirmability. Data analysis techniques using the Miles and Huberman approach in 1984 include data reduction, data presentation (display), and drawing conclusions (conclusion drawing/verification). Based on the results of the research, the mathematical concepts contained in the process of making Daluang paper in Indramayu Regency are the geometry of the building of the tube chamber, the geometry of building the block room, the geometry of the rectangular flat building, the geometry of the circular flat building, the geometry of the trapezoidal flat building, measurements, comparisons, and angles.